Indirect predator effects influence behaviour but not morphology of juvenile coral reef Ambon damselfish Pomacentrus amboinensis. Issue 2 (1st April 2021) - Arvizu, Brittany; Allan, Bridie J. M.; Rizzari, Justin R.
Abstract: A 6‐week laboratory experiment exposed juvenile Ambon damselfish Pomacentrus amboinensis to visual and chemical cues of either a predator, a herbivore or a null control (sea water) and found no effect of predator cues on prey morphology (proportion of ocellus to eye diameter, body depth, standard length and fin area). Nonetheless, behaviour was significantly affected by predator presence, with prey less active and taking half as many feeding strikes when exposed to predators compared to fish from the null control. The presence of a herbivore also affected prey behaviour similar to that of the predator, suggesting that the presence of a non‐predator may have important effects on development.